Penguatan Pendidikan Akhlak dan Spiritualitas Santriwati di TMI Al-Amien Prenduan - Ruslan Ruslan; Mepa Arianti; Moh Wardi (Tafhim Al-'Ilmi, 2021)
AbstractThis study aims to describe the model of moral education in an effort to shape the spirituality offemale students at TMI Al-Amien Prenduan, and what are the factors that cause violations ofreligious norms by these female students. By using descriptive qualitative techniques, datacollection techniques through field methods, observations, interviews and observations werecarried out as an initial meeting to collect data. The results showed that the moral and spiritualstrengthening of female students using the Tadzkira model with an acronym explanation or anabbreviation of T = tunjukan teladan, A = arahkan (berikan bimbingan) D = dorongan (denganmemberikan motivasi dan nasehat-nasehat). Z = zakiyah (murni-suci-bersih) K = kontinuitas(pembiasaan dalam berbuat, bersikap dan bertindak) I = ingatkan (mengingatkan dalam segala halyang melenceng dari syari’at islam) R = pengulangan. A = aplikasikan (mempraktekkan dikehidupan sehari-hari)..Kata Kunci: Pendidikan, Akhlak, Spiritualitas.